2017
DOI: 10.1155/2017/7326107
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chunghyul‐Dan, an Agent of Korean Medicine, on a Mouse Model of Traumatic Brain Injury

Abstract: Chunghyul-Dan (CHD) is the first choice agent for the prevention and treatment of stroke at the Kyung Hee Medical Hospital. To date, CHD has been reported to have beneficial effects on brain disease in animals and humans, along with antioxidative and anti-inflammatory effects. The aim of this study was to evaluate the pharmacological effects of CHD on a traumatic brain injury (TBI) mouse model to explore the possibility of CHD use in patients with TBI. The TBI mouse model was induced using the controlled corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Together with CAPE, they exhibited potent anti-proliferative and proapoptotic properties. Currently, CAPE is one of the most promising compounds [ 4 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Together with CAPE, they exhibited potent anti-proliferative and proapoptotic properties. Currently, CAPE is one of the most promising compounds [ 4 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other doses, 3 and 30 mg/kg, were selected at three time intervals (low dose and high dose). The positive control condition used in the current study, minocycline, has been reported to have protective effects against various brain injuries including TBI [36,37]. The dose of 45 mg/kg was chosen based on a previous report [36].…”
Section: Discussionmentioning
confidence: 99%
“…The TBI model was induced according to the modified CCI protocol [36]. Briefly, ICR mice were anesthetized with isoflurane (2 %).…”
Section: Tbi Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were randomly assigned to each experimental groups. In vivo model of TBI was induced using the CCI method 32,33 . Briefly, ICR mice (8 weeks old, male, 30–33 g) were anesthetized with 2% isoflurane in gas mixture of 70% N 2 O and 30% O 2 , and placed in the stereotaxic frame.…”
Section: Methodsmentioning
confidence: 99%